1975
DOI: 10.1149/1.2134174
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Catalyzed Anodes for Hydrazine Fuel Cells: II . Lifetime Studies of Heat‐Treated Nickel Boride Catalyzed Anodes

Abstract: The potential‐time relationship of nickel boride catalyzed anodes for the electrochemical oxidation of hydrazine is different from that relationship for similarly catalyzed hydrogen anodes. The potential of freshly catalyzed, nickel boride hydrazine anodes exhibits a decay with time. Chemical, electrochemical, and microscopic analyses related the rate of boron loss from the anode to the rate of decay of the anodic potential. By subjecting the anode to a mild heat‐treatment, considerable improvement in the lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Meibuhr et al evaluated NiB/Ni electrodes for the HHOR 208 and found that surfaces reduced for 1 hour in a mixture of 6% H2 in Ar at mild temperature (93°C) were the most durable in operation, which was explained by their optimal retention of boron in such a reduced NiB layer. 209 Considering the above-cited study of the BOR (see gas". 216 This selected literature review demonstrates that there is some merit to combine Ni with other elements, notably to improve its capability to remain in "reduced" state of surface.…”
Section: Hydrazinementioning
confidence: 99%
See 2 more Smart Citations
“…Meibuhr et al evaluated NiB/Ni electrodes for the HHOR 208 and found that surfaces reduced for 1 hour in a mixture of 6% H2 in Ar at mild temperature (93°C) were the most durable in operation, which was explained by their optimal retention of boron in such a reduced NiB layer. 209 Considering the above-cited study of the BOR (see gas". 216 This selected literature review demonstrates that there is some merit to combine Ni with other elements, notably to improve its capability to remain in "reduced" state of surface.…”
Section: Hydrazinementioning
confidence: 99%
“…Many studies followed this initial report, aiming at optimizing the HHOR performance. Meibuhr et al evaluated NiB/Ni electrodes for the HHOR and found that surfaces reduced for 1 h in a mixture of 6% H 2 in argon at mild temperature (93 °C) were the most durable in operation, which was explained by their optimal retention of boron in such a reduced NiB layer . Considering the above-cited study of the BOR (see section ), strong dependence of the HHOR activity on the extent of oxidation of the Ni surface might represent an alternative explanation.…”
Section: Oxidation Of Complex Fuels On Nickel-based Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pungor et al (4)(5)(6)(7) and independently, Rechnitz et al (8,9), describe a halide-sensitive membrane obtained with fine particles of silver halide contained in a polymerized silicon rubber matrix. Mascini and Liberti (10) prepare a memb~"~ne pressing at 130 ~ 150~ a mixture of silver halide and thermoplastic polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no instrumental technique which can satisfactorily monitor H and MMH and meet the requirements for protection of personnel during handling and storage of these chemicals (6). Therefore, since previous studies of hydrazine as fuel cell fuels (7,8) had demonstrated the ability to electrooxidize these compounds, we decided to investigate the electrochemical technique as the basis for a hydrazine instrument (9).…”
mentioning
confidence: 99%